Morphohistological observations on testicle and spermatozoa of Microlophus peruvianus (Lesson, 1826) (Sauria:Tropiduridae) - Ramírez, Cesar (2006)
The present work provides morphological and histological information of the testicles and spermatozoon of 5 specimens of the Peruvian small lizard Microlophus peruvianus (Lesson, 1826), from Huaral, Lima (11º 26´S; 77º24´W); collected during September, 2005. The fieldwork was combined with the gonads analysis at the laboratory. The snout-sewer length average was 91,3mm ± 13.655; all specimens deals a great spermatogenic meiotic activity showing a germinative epithelium thickness of 126.33 mμ ± 0.092, which suggests that the month of collect would be within its active cycle of reproduction. The spermatogenic cells present the typical cellular types of the spermatogenesis: spermatogonias (3.544 mμ ± 0.4513), primary espermatocitos (4.864 mμ ± 0.5292), spermatids (2.85 mμ ± 0.4071); No secondary spermatocytes where founded. The morphology and biometry of the spermatozoon of M. peruvianus proposes its importance as taxonomic value.